(7+(-b))+(3b+2)=

Simple and best practice solution for (7+(-b))+(3b+2)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (7+(-b))+(3b+2)= equation:


Simplifying
(7 + (-1b)) + (3b + 2) = 0

Remove parenthesis around (7 + (-1b))
7 + (-1b) + (3b + 2) = 0

Reorder the terms:
7 + (-1b) + (2 + 3b) = 0

Remove parenthesis around (2 + 3b)
7 + (-1b) + 2 + 3b = 0

Reorder the terms:
7 + 2 + (-1b) + 3b = 0

Combine like terms: 7 + 2 = 9
9 + (-1b) + 3b = 0

Combine like terms: (-1b) + 3b = 2b
9 + 2b = 0

Solving
9 + 2b = 0

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '-9' to each side of the equation.
9 + -9 + 2b = 0 + -9

Combine like terms: 9 + -9 = 0
0 + 2b = 0 + -9
2b = 0 + -9

Combine like terms: 0 + -9 = -9
2b = -9

Divide each side by '2'.
b = -4.5

Simplifying
b = -4.5

See similar equations:

| 0.0015= | | 5(6K-10)=10(k-25) | | %=793,000 | | 9x-35=63 | | -85+5x=59-x | | 6(2x+1)-2(5x+2)=0 | | 1.7x-3=-1.3 | | 120.80=3.20+57.20 | | 2sin^3x-sin^2x-2sinx-1=0 | | n-6n+8=0 | | 2sin^3x+sin^2x-2sinx+1=0 | | x^10=74 | | 9x-68=52-x | | (k+2)=16 | | 3(j+4)=35 | | 2a^2-2a+99=0 | | 5x^2-4x-460=0 | | 6(5-2x)-8=106 | | -5x-96=-10x+34 | | 5x^2-4x-461=0 | | 24-49x-6-9x=2-30x | | (m-2)=5 | | 3y-12x+6=o | | 25x-4=3x^2+8x+16 | | -1x+-5=25 | | -7-k=7-3k | | 3y=6+6x | | 16+6=x-70 | | 12-3y=14 | | -294-(-70)= | | 10x+70+7x=13+x | | (m-7)=49 |

Equations solver categories